A Nonrandomized Controlled Trial of Strengths Model Case Management in Hong Kong. (July 2019) - Tsoi, Emily W. S.; Tse, Samson; Yu, Chong-Ho; Chan, Sau-Kam; Wan, Eppie; Wong, Stephen; Liu, Lucia
Purpose: This study evaluates the effectiveness of the strengths model of case management (SMCM) for people with severe mental illness in Hong Kong. This is the first controlled trial outside the United States to investigate the impacts of SMCM on caseworkers as well as service users alongside fidelity measures. Method: Service users and their caseworkers were recruited from three types of supported accommodation for this 12-month nonrandomized controlled trial. Mixed modeling was used to investigate within-subject differences. Results: Results indicated that SMCM was effective in helping users progress toward their recovery goals and in alleviating emotional exhaustion among caseworkers. However, it was ineffective in improving, hope, well-being, work alliance, and psychiatric symptoms. High intervention fidelity was associated with positive outcomes. Conclusions: Conceptually, SMCM has the potential to improve service users' functional but not personal recovery. It is also potentially conducive to the well-being of caseworkers.